PKM Peningkatan Kemampuan E-Marketing Kepada Staff Nanuk’s Bungalows, Nusa Lembongan, Klungkung - I Made Astu Mahayana; Gde Deny Larasdiputra; Ni Made Suwendri (Postgraduated Community Service Journal, 2024)
This community service program aims to explore the opportunities and transformative impact digitalization can have on Small and Medium Enterprises (SMEs), particularly the tourism sector in Lembongan Island, Bali. The integration of Information and Communication Technology (ICT) and social media platforms, such as Instagram, has revolutionized traditional marketing strategies, enabling SMEs to effectively promote their products and services to a global audience. Through hands-on training in digital marketing, including product photography and content & caption writing, local entrepreneurs were prepared to increase their online presence and interact with customers more effectively. The program highlights that the utilization of digital tools and techniques not only expands market reach but also improves operational efficiency and competitiveness. In addition, the importance of the power of bonding in facilitating purchasing decisions and driving word-of-mouth marketing was underscored. As SMEs navigate the digital realm, continued skills development and strategic use of social media are critical to achieving sustainable business growth and contributing to the local economy. This program is expected to continue and grow, and can serve as a reference for innkeepers in utilizing language and digital marketing with the aim of increasing income and market reach towards international success.